2020
DOI: 10.2196/17441
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Library for Increasing Awareness About Living Donor Kidney Transplants: Formative Study

Abstract: Background It is not common for people to come across a living kidney donor, let alone consider whether they would ever donate a kidney themselves while they are alive. Narrative storytelling, the sharing of first-person narratives based on lived experience, may be an important way to improve education about living donor kidney transplants (LDKTs). Developing ways to easily standardize and disseminate diverse living donor stories using digital technology could inspire more people to consider becomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…19 This study's results align with other research about LDKT decision-making, showing that many donors pursuing KPD also decide quickly, almost instantaneously, to participate without systematically processing all the information. 20,21 There is much more to understand when deciding whether to pursue KPD, with transplant coordinators previously reporting that KPD education is more logistically complex to explain. 12 Results of this study support that patients also find the logistics of KPD difficult to understand.…”
Section: Discussionmentioning
confidence: 99%
“…19 This study's results align with other research about LDKT decision-making, showing that many donors pursuing KPD also decide quickly, almost instantaneously, to participate without systematically processing all the information. 20,21 There is much more to understand when deciding whether to pursue KPD, with transplant coordinators previously reporting that KPD education is more logistically complex to explain. 12 Results of this study support that patients also find the logistics of KPD difficult to understand.…”
Section: Discussionmentioning
confidence: 99%
“…The use of "live donor champions" may also enable discussions to start: in this approach, a friend or family member is trained to undertake an advocate role, sharing information on the patient's behalf with the patient's wider social network [43]. Other approaches that may overcome "cultures of silence" include people with kidney disease, transplant recipients and donors sharing their experiences on an open web-platform such as healthtalk.org (http://healthtalk.org) and the living donation storytelling project (https://explorelivingdonation.org/) [44]. However, such approaches need to be formally evaluated for effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the potential of storytelling for transplant education, we designed and built a digital storytelling library of LDKT stories from a diverse set of real living donors, recipients, and their family and friends [30]. Over 80% reported that they were motivated by a desire to educate the public about living donation, show people how living donation can make a difference for both the recipient and donor, and help others looking for more information about living donation.…”
Section: Educational Barriers To Transplant In Dialysis Centersmentioning
confidence: 99%